The Influence of Financial Literacy and Digital Wallet Usage on Financial Behavior Among Students: An Empirical Study of Students in South Jakarta - Revaldo Revaldo; Mukti Soma (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study evaluates the influence of financial literacy and the use of e-wallets on the financial behavior of students in South Jakarta, focusing on both individual effects and the interaction between these factors. A quantitative approach was employed within an explanatory-causal framework, with primary data collected through a 1-4 Likert scale questionnaire distributed to 400 students residing or studying in the area, selected via purposive sampling. The analysis included instrument quality assessment, descriptive statistics, classical assumption testing, multiple linear regression, as well as t-tests and F-tests. Findings indicate that financial literacy does not exert a significant influence on students' financial behavior, with a significance value of 0.178, exceeding the 0.05 threshold. In contrast, e-wallet usage demonstrates a notable positive impact, evidenced by a significance value of 0.000, which is below 0.05, along with a positive regression coefficient. When assessed together, both factors significantly affect financial behavior, as shown by an F value of 902.144 and a significance level of 0.000. The Adjusted R Square value of 0.819 suggests that 81.9% of the variance in students' financial behavior can be attributed to financial literacy and e-wallet usage, while the remaining 18.1% is influenced by other variables not examined in this study. These results emphasize the greater role of e-wallet usage in shaping financial practices among students compared to financial literacy. Therefore, it is recommended that digital financial literacy initiatives be enhanced, focusing on the development of record-keeping skills, expenditure management, and responsible use of digital transaction tools.